Parenting by mothers from marginalized communities and the role of socioeconomic disadvantage: insights from marginalized Roma communities in Slovakia - Van Laer, Stanislava; Fiľakovská Bobáková, Daniela; Kolarcik, Peter; Engel, Ofer; Madarasová Gecková, Andrea; Reijneveld, Sijmen A.; de Kroon, Marlou L. A. (Frontiers in Psychology, 2024)
Background Roma living in marginalized communities often face poor living conditions and material deprivation, which may negatively impact parenting. Our aim is to compare the parenting behavior (support, harsh discipline, and stimulation) of mothers from marginalized Roma communities and the majority population in Slovakia. We also examine the role of socioeconomic disadvantage and related worries in the differences in parenting behavior between these groups. Methods We obtained cross-sectional data from mothers of children aged 14–18 months using the first wave of the longitudinal RomaREACH study dataset. Two groups were included in the sample: 93 mothers from MRCs and 102 mothers from the majority. We performed multiple regression and mediation analyses to assess whether the educational level of mothers, the degree of poverty, and poverty-related feelings of stress and worries explain parenting behavior differences between the groups of mothers. Results We found significant differences in parenting, especially in harsh disciplining and stimulation. These two domains were significantly associated with maternal education, degree of poverty, and poverty-related stress and worries. The degree of poverty partially mediated stimulation differences between the two groups of mothers. Conclusion Parenting in MRCs seems harsher and less stimulative than parenting in the Slovak majority. These differences are associated with the socioeconomic disadvantage of mothers. The degree of poverty partially explains why parenting in MRCs is less stimulative. These results may inform intervention efforts aimed at disadvantaged families.